KUALITAS KARKAS AYAM PEDAGING YANG DIBERI RANSUM MENGANDUNG LIMBAH SAWI - Londok, Jola J.M.R.; Rompis, John E.G.; Mangelep, Claudya (ZOOTEC, 2017)
ABSTRACT CARCASS QUALITY OF BROILERS FED RATION CONTAINING WASTE OF SAWI. Study was conducted to evaluate the effect of substituting part of ration with sawi waste meal on carcass quality and abdominal fat of broilers. Total of sixty unsexed day old chick broilers of MB-202 P strain were randomly divided into twenty units of pens, each of pen was filled with three heads of chicks. Birds were maintained during forty days. Levels of substituting part of ration with sawi waste meal were 0, 5, 10, 15, and 20 percents. Each treatment had four replications using completely randomized design with 5 x 4. Fresh water and ration were given ad libitum. Birds from day old chick to the age of twenty one days old were fed with BR-21E ration for all treatments. The treatments of ration were fed at ages of twenty two days old to the end of study (period when all animals were slaughtered). Data were analyzed using F test and Tukey test for the significant F test. Results showed that control treatments were significantly different (P<0.05) with those others four treatments for carcass weight, but not significantly different with those others four treatments for carcass percentages and abdominal fat. Therefore, sawi waste meal can be used to substitute part of ration up to 20 percents for broilers ration in term of the carcass percentages and abdominal fat. Key words: Sawi waste meal, broilers, carcass quality.